(untitled) (Spectrum Journal of Innovation, Reforms and Development, 2023)
A volleyball player at the stage of specialization must have good speed training. This is expressed in running qualities. Running makes high demands on the athlete, he must have excellent physical fitness, be strong, fast, well-coordinated.